Bacillus strain BX77: a potential biocontrol agent for use against foodborne pathogens in alfalfa sprouts - Gollop, Rachel; Kroupitski, Yulia; Matz, Ilana; Chahar, Madhvi; Shemesh, Moshe; Sela Saldinger, Shlomo (Frontiers in Plant Science, 2024)
Despite regulatory and technological measures, edible sprouts are still often involved in foodborne illness and are considered a high-risk food. The present study explored the potential of spore-forming Bacillus isolates to mitigate Salmonella and Escherichia coli contamination of alfalfa sprouts. Food-derived Bacillus strains were screened for antagonistic activity against S. enterica serovar Typhimurium SL1344 (STm) and enteropathogenic E. coli O55:H7. Over 4 days of sprouting, levels of STm and E. coli on contaminated seeds increased from 2.0 log CFU/g to 8.0 and 3.9 log CFU/g, respectively. Treatment of the contaminated seeds with the most active Bacillus isolate, strain BX77, at 7 log CFU/g seeds resulted in substantial reductions in the levels of STm (5.8 CFU/g) and E. coli (3.9 log CFU/g) in the sprouted seeds, compared to the control. Similarly, co-culturing STm and BX77 in sterilized sprout extract at the same ratio resulted in growth inhibition and killed the Salmonella. Confocal-microscopy experiments using seeds supplemented with mCherry-tagged Salmonella revealed massive colonization of the seed coat and the root tip of 4-day-old sprouted seeds. In contrast, very few Salmonella cells were observed in sprouted seeds grown with BX77. Ca-hypochlorite disinfection of seeds contaminated with a relatively high concentration of Salmonella (5.0 log CFU/g) or treated with BX77 revealed a mild inhibitory effect. However, disinfection followed by the addition of BX77 had a synergistic effect, with a substantial reduction in Salmonella counts (7.8 log CFU/g) as compared to untreated seeds. These results suggest that a combination of chemical and biological treatments warrants further study, toward its potential application as a multi-hurdle strategy to mitigate Salmonella contamination of sprouted alfalfa seeds.